Analisis Peran Pemilik Objek Pariwisata dalam Meningkatkan Kualitas Pelayanan di Lembah Curugan Gunung Putri - Mohammad Zein Alfiansyah (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to investigate the involvement of tourism site owners in enhancing the service quality at Lembah Curugan Gunung Putri. A qualitative approach with a descriptive method was employed in this research. Four key informants were selected purposively, including the owner, manager, a full-time staff member, and a daily worker. Data collection was carried out through in-depth interviews, direct observation, and document analysis. The findings reveal that the owner's role in improving service quality has not been fully optimized. The main contributing factors are the lack of effective communication between the owner and the staff, as well as insufficient facilities and infrastructure.